A Case Study to Address: "Is Your Pulsed Laser Deposition Chamber Clean?". Issue 9 (25th May 2021) - Dumen, Manish; Kaur, Ripudaman; Goyal, Saveena; Tomar, Ruchi; Wadehra, Neha; Chakraverty, Suvankar
Abstract: Pulsed laser deposition (PLD) is one of the important techniques for the growth of oxide thin films, interfaces, and superlattices. It can also be utilized to implement diverse combinatorial approaches. Thin film growth using PLD hinges on various parameters that decide the composition, structure, quality, and finally the physical properties of the films, interfaces, and superlattices. In this paper it is demonstrated how the growth conditions inside the chamber during the growth can be judged from outside by combining in situ and ex situ techniques. An example of the growth of LaVO3 ‐SrTiO3 interface is given to elucidate the effect of repetitive growth on the chamber condition and hence on the reproducibility of the physical properties of the samples. The experiments suggest noticeable change in transport properties with successive deposition processes. Abstract : A different approach is used to monitor the growth condition of pulsed laser deposition system with higher reliability. After thousands of depositions in the system with the time, the different viewports get dirty and thus the physical properties of the material can be changed significantly due to the change in the growth condition inside the chamber.